Preparation and immunological characterization of an inactivated canine Clostridium perfringens type A vaccine. (1st November 2019) - Xing, J.; Ji, X.; Sun, Y.; Zhu, L.; Jiang, Q.; Guo, X.; Liu, J.
Abstract: Clostridium perfringens is the main cause of sudden death in dogs and currently there is no vaccine to prevent it. In this study, a canine C. perfringens type A strain was used to prepare a vaccine. C. perfringens was inactivated by formaldehyde and adjuvants were added. The safety and immunological characteristics of the inactivated C. perfringens vaccine were evaluated in mice and dogs. The results showed that the C. perfringens vaccine was safe and had immunoprotective activity. The serum antibody titre of immunized mice reached up to 6·25 × 10 4 . Both single immunization of 4 ml and dual immunizations of 2 ml each provided good immune protection, with five of five immunized dogs surviving. This study also studied a detoxified crude α ‐toxin extract vaccine. The results showed that a single immunization with 0·5 ml of the detoxified crude α ‐toxin extract vaccine provided immune protection, with five of five immunized dogs surviving. The inactivated C. perfringens type A vaccine can be used to prevent canine C. perfringens infections. Significance and Impact of the Study: Clostridium perfringens is the main cause of sudden death in dogs and currently there is no vaccine to prevent it. In this study, an inactivated canine C. perfringens vaccine and a detoxified crude α ‐toxin vaccine were prepared. The safety and protective effects of these vaccines were evaluated using mouse and dog models. The vaccines were shown to be safe and to provide immune protection effects that can be used to prevent canine C. perfringens infection.